THE SCIENTIFIC ANALYSIS OF ZAMZAM WATER IN THE PERSPECTIVE OF HADITH PROPHET MUHAMMAD SAW - Husnah Lutfiah (AS-SALAM, 2020)
This research is motivated by the rapid development of natural science and research conducted by scientists. We already know that Zamzam water is the best water on this earth according to the hadith of the prophet Muhammad SAW. Therefore, the authors are interested in researching and studying more deeply about zamzam water based on the hadith of the Prophet Muhammad and science. This research is a library research with its primary data source as the Complete Hadith Index by Ahmad Zacky El-Syafa and supported by international journals. The data management techniques use qualitative data analysis, while the techniques and data analysis steps are describing, collecting and outlining.